2013
DOI: 10.1038/nphoton.2013.128
|View full text |Cite
|
Sign up to set email alerts
|

Towards quantum-dot arrays of entangled photon emitters

Abstract: To make photonic quantum information a reality 1,2 , a number of extraordinary challenges need to be overcome. One of the outstanding challenges is the achievement of large arrays of reproducible "entangled" photon generators, maintaining the compatibility with integration with optical devices and detectors 3,4,5 . Semiconductor quantum dots (QDs) are potentially ideal for this. They allow generating photons on demand 6,7 without relying on probabilistic processes 8,9 . Nevertheless, most QD systems are limite… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
211
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 204 publications
(224 citation statements)
references
References 31 publications
6
211
1
1
Order By: Relevance
“…10,11 A noteworthy advantage of this approach is the fabrication of arrays of devices, as recently demonstrated in Ref. 12, where entangled photon emission from an array of In 0.25 Ga 0.75 As nanostructures was reported.…”
Section: Introductionmentioning
confidence: 93%
“…10,11 A noteworthy advantage of this approach is the fabrication of arrays of devices, as recently demonstrated in Ref. 12, where entangled photon emission from an array of In 0.25 Ga 0.75 As nanostructures was reported.…”
Section: Introductionmentioning
confidence: 93%
“…58 However, these methods do not allow the control of the position and even the size of the nanostructures, which is an essential requirement for applications such as single photon emitters. 59 This growth method of InGaN/GaN nanorods provides a template to allow for wafer-scale position controlled growth of InGaN QD arrays as demonstrated by Juska et al 60 for InGaAs QDs grown in inverted pyramidal arrays.…”
Section: Resultsmentioning
confidence: 99%
“…In a more refined operation mode employing biexcitons, the Coulomb-bound four-carrier states containing two electrons and two holes, quantum dots can provide pairs of photons emitted in a fast cascade very similar to the original atomic cascade experiment by Aspect et al [2]. It has been demonstrated that in the absence of the fine structure splitting of the bright exciton levels, such a cascade exhibits polarization entanglement [3][4][5][6][7][8]. Entanglement of photons is a fundamental resource for long distance quantum communications [9,10], where it forms the central part of various quantum communication protocols like teleportation [11] and entanglement swapping [12].…”
mentioning
confidence: 82%